Directors' liability in negligence to third parties: challenging the assumption of responsibility approach. (2nd January 2016) - Stace, Victoria
ABSTRACT: What is the role of 'assumption of responsibility' when determining directors' liability in negligence to third parties? A recent decision of the English High Court of Justice confirms that, so far as the English courts are concerned, 'assumption of responsibility' is a threshold test for establishing liability. This test requires conduct that would lead a third party to conclude that the director intended to assume personal responsibility. However recent academic writing argues that assumption of responsibility is not a threshold test, but rather a subset of proximity. This note suggests that a preferable approach, which is the approach taken by New Zealand courts, is to apply a two-stage proximity plus policy inquiry, which enables the court to address policy considerations relevant to imposing liability on directors.